Growth, physicochemical and quantum chemical investigations on 2-amino 5-chloropyridinium 4-carboxybutanoate – an organic crystal for biological and optoelectronic device applications. Issue 112 (22nd November 2016) - Babu, B.; Chandrasekaran, J.; Mohanbabu, B.; Matsushita, Yoshitaka; Saravanakumar, M.
Abstract : Optically transparent organic single crystals of 2-amino 5-chloropyridinium 4-carboxybutanoate (2A5C4C) with sizes of 7 × 4 × 2 mm 3 were grown by a slow evaporation solution growth technique at room temperature using methanol solvent. Abstract : Optically transparent organic single crystals of 2-amino 5-chloropyridinium 4-carboxybutanoate (2A5C4C) with sizes of 7 × 4 × 2 mm 3 were grown by a slow evaporation solution growth technique at room temperature using methanol solvent. The lattice parameter values of the crystals were evaluated by single crystal XRD; the results confirmed that 2A5C4C crystal belongs to the orthorhombic system with cell parameters of a = 5.1858 Å, b = 14.501 Å and c = 15.963 Å. The crystalline phases and quality of the grown crystals were ascertained by powder XRD and high resolution XRD (HRXRD) studies, respectively. The crystal structure and various functional groups present in 2A5C4C were confirmed by 1 H, 13 C NMR and FTIR analysis. The optical absorption, transmittance and lower cutoff wavelength were identified by UV-Vis-NIR studies. The optical band gap was estimated from the Tauc plot and was found to be about 3.68 eV. The charge transport mechanism and photoconducting nature of 2A5C4C were analyzed using dielectric and photoconductivity studies, and the obtained results were compared with previously reported values. In order to analyze the thermal and mechanical stability properties of the 2A5C4C crystal, TG/DTA and Vickers microhardness studies were performed. The laser-induced surface damage threshold values for the grown crystal were measured using a Nd:YAG laser. Powder SHG analysis was also carried out for powder samples using the Kurtz and Perry powder second harmonic generation (SHG) technique; the results were compared with KDP as a reference. The theoretical molecular electrostatic potential, HOMO–LUMO, natural bonding orbital analysis (NBO) and first hyperpolarizability values of the 2A5C4C molecule were calculated and discussed in detail. Moreover, the hydrogen bonded charge transfer crystal was screened for its pharmacological antioxidant activity against 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and hydrogen peroxide (H2 O2 ) radicals.